Theoretical Analysis and Modelling of LNG Reforming to Hydrogen Marine Fuel for FLNG Applications - We Lin Chan; Ivan C. K. Tam; Arun Dev (Gases, 2025)
The LNG maritime industry started to anticipate offshore LNG production in tandem with increasing demand for FLNG platforms as offshore gas resources were developed further. The rapid expansion of FLNG deployment demands equipment and procedures that handle challenges associated with weight and space constraints. The chemical composition of LNG will result in slightly fewer CO2 emissions. While not significant, another crucial aspect is that LNG predominantly comprises methane, which is acknowledged as a greenhouse gas and is more harmful than CO2. This requires investigation into clean energy fuel supply for power generation systems, carbon emissions from the process, and thermodynamic analysis and optimisation. Focus on supplying fuel for FLNG power generation to reduce the essential management of boil-off fuel gas, which can be researched on the direct reforming method of hydrogen as a marine fuel gas to support the power generation system. The principal reason for choosing hydrogen over other energy sources is its exceptional energy-to-mass ratio (H/C ratio). The most effective method for hydrogen production is the methane reforming process, recognised for generating significant quantities of hydrogen. To optimise the small-scale plant with a carbon capture system (CCS) as integrated into the reforming process to produce blue hydrogen fuel with zero carbon emissions, this research selection focuses on two alternative processes: steam methane reforming (SMR) and autothermal reforming (ATR). Furthermore, the research article will contribute to other floating production platforms, such as FPSOs and FSRUs, and will be committed to clean energy policies that mandate the support of green alternatives in substitution of hydrocarbon fuel utilisation.